Application of Augmented Reality-Based Learning Media to Improve Understanding of Basic Movements in View of Learning Style - Nurkadri; Novita; Asep Suharta; Amansyah; Dian Pujianto (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Although AR technology has great potential to improve learning experiences and outcomes, its application in the context of education, especially in PJOK learning, is still limited. Many schools and educational institutions have not optimally utilized this technology to deliver learning materials. This study aims to analyze the application of augmented reality-based learning media to improve understanding of basic movements in terms of student learning styles. This type of research is an experimental study of The One-Group Pretest-Posttest with one-way ANOVA test. The research sample amounted to 20 people consisting of 10 men and 10 women. Data were collected using a test data collection method with an instrument in the form of a test sheet. The results of the visual learning style research have values that fall into the high improvement category, while auditory and kinesthetic learning styles have values that fall into the medium improvement category. The conclusion on the results of the one-way ANOVA test to measure the hypothesis test of the significance value of the interaction of the use of AR-based media. Through AR media, it can be seen that the comprehension ability of students who have kinesthetic and visual learning styles is greater than auditory students.This research has important positive implications for educational development. The research findings can encourage the development of other technology-based learning media that can be applied to various student learning styles.